1997
DOI: 10.3168/jds.s0022-0302(97)76121-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of the Mammary Gland

Abstract: The mammary gland is a complex organ that provides neonatal offspring with milk for nourishment and disease resistance. Specific and innate immune factors associated with mammary gland tissues and secretion also play a vital role in protecting the gland from infectious disease. Through genetic selection and technological advances in milk removal, the bovine mammary gland yields for more milk than is needed to nourish the newborn calf. This excess is the basis of the dairy industry. Factors associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
311
1
61

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(378 citation statements)
references
References 77 publications
5
311
1
61
Order By: Relevance
“…In the mammary gland, the GM-CSF factor activates macrophages and neutrophils [33] and improves chemotactic action and peroxidase production from neutrophils [19], whilst interleukin-2 enhances the phagocytic ability of macrophages and participates in the initial immune response in the mammary gland [18,66], therefore, playing a role in the defence mechanisms of the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammary gland, the GM-CSF factor activates macrophages and neutrophils [33] and improves chemotactic action and peroxidase production from neutrophils [19], whilst interleukin-2 enhances the phagocytic ability of macrophages and participates in the initial immune response in the mammary gland [18,66], therefore, playing a role in the defence mechanisms of the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Specific immunity consists of antibodies, macrophages (antigen-presenting cells) and T and B lymphocytes that recognize specific microorganisms (Sordillo et al, 1997). The T cells can be sub-divided into T-helper and T-cytotoxic lymphocytes.…”
Section: General Aspects Of the Immune Responsementioning
confidence: 99%
“…The cytotoxic T cells recognize and eliminate cells infected with an antigen, and old or damaged immune cells that, if present, can increase the susceptibility to infections. The B lymphocytes differentiate into plasma cells that produce antibodies or immunoglobulins (Igs), that is, IgG 1 , IgG 2 and IgM, or memory cells (Sordillo et al, 1997). Both the innate and the specific immunity have a broad diversity of mechanisms.…”
Section: General Aspects Of the Immune Responsementioning
confidence: 99%
“…During the development of mastitis, in the cow as well as in the sow, it has been shown that the proinflammatory cytokines not only provide defence against bacterial infections, but also contribute to the clinical symptoms of disease [5,30,44,46,49,50,59]. For instance, it has been established that IL-1β, IL-6, IL-8, and TNF-α play a role in the initiation of the inflammatory responses following intramammary inoculation with Escherichia coli [6,45,48,59].…”
Section: Introductionmentioning
confidence: 99%